Analisis Strategi Harga dan Kualitas Pelayanan terhadap Kepuasan Pelanggan pada Bisnis Kopi Kekinian - Dzaky Raditya; Fadilla Al Hapis; Salwa Salsabila; Zainarti Zainarti (JURNAL ILMIAH EKONOMI DAN MANAJEMEN, 2026)
This study aims to analyze the influence of pricing strategy and service quality on customer satisfaction in contemporary coffee shops. The growth of the modern coffee industry encourages businesses to optimize competitive pricing and quality service to maintain customer loyalty. The research method used was quantitative, with a survey approach using a questionnaire to 100 respondents, customers of contemporary coffee shops. The results showed that pricing strategy had a significant effect on customer satisfaction, while service quality had a stronger influence. The combination of the two contributed positively to increasing customer satisfaction and loyalty. These findings indicate that contemporary coffee businesses need to optimize the alignment of prices with perceived value and improve the quality of frontline service to maintain competitiveness.